2017
DOI: 10.1007/s12053-017-9543-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoting energy-saving behaviour: formal social groups as promising middle actors for municipal interventions

Abstract: City governments worldwide are trying to motivate their citizens to reduce their energy use-a particular challenge as they try to reach individual households. A promising strategy to engage the public broadly entails collaborating with middle actors to multiply the effects of municipal interventions. Some of these middle actors are formal social groups (e.g. sports clubs and neighbourhood associations). We conducted an online experiment (N = 136) to determine whether such interventions were more effective when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Energy-efficient technologies, such as LFSHs, can be promoted through behavioural interventions [26,29]. A large body of literature has evaluated different intervention approaches, such as feedback [30,31], information [32], goal setting [33] and social influence [34][35][36]. To promote energy efficient technologies, increasing attention has been directed towards social influence approaches, including social norms [34].…”
Section: What Influences Decisions To Purchase Lfshs In a Specific Comentioning
confidence: 99%
“…Energy-efficient technologies, such as LFSHs, can be promoted through behavioural interventions [26,29]. A large body of literature has evaluated different intervention approaches, such as feedback [30,31], information [32], goal setting [33] and social influence [34][35][36]. To promote energy efficient technologies, increasing attention has been directed towards social influence approaches, including social norms [34].…”
Section: What Influences Decisions To Purchase Lfshs In a Specific Comentioning
confidence: 99%
“…Therefore, group members may react more positively towards energysaving programmes when communicated by their own group rather than by a city administration. Accordingly, Frick et al (2017) demonstrated in an online experiment that participants were more motivated to follow an energy-saving programme when addressed by their formal social group compared to being addressed by their municipal administration.…”
Section: Introductionmentioning
confidence: 99%
“…However, those who participate in such programmes are often already aware of their energy consumption and are active in saving energy (Sütterlin, Brunner, & Siegrist, 2011). One interesting approach for attracting new target groups when motivating behavioural change is collaborating with formal social groups, such as sports clubs (Seidl, Moser, & Blumer, 2017, Frick, Seidl, Stauffacher, & Moser, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations